Elaboración de la guía didáctica sobre movimientos, ángulos y planos de fotografía y video mediante la utilización del laboratorio multimedia de la carrera de diseño gráfico computarizado de la Universidad Técnica de Cotopaxi, en el período 2014 - Bautista Bastidas, Kléber Alexis (2015)
At present and by a careful study we notice the necessity to design a Didactic Guide on the movements, angles, planes photographic , and videos in order to students know about proper management of laboratory equipment in the Computerized Design Career at the Technical University of Cotopaxi, strengthening knowledge and learning at the same time in the students. Nowadays Didactic Guides with illustration are essential in Pedagogy so they are used in many places around the world, in this way we can get students’ attention and get favorable academic results. In the Multimedia Lab we can find latest technology equipment that require the use and mastery of proper techniques, in this case the contents of a tutorial must be clear and precise using easy elements of identification for the students like printing, pictures in good quality, color range, illustrations concerning to the subject, in this way the teacher can be better connected with the contribution of this material.